2020
DOI: 10.25077/jpi.22.2.211-217.2020
|View full text |Cite
|
Sign up to set email alerts
|

Perendaman Rumput Laut Turbinaria murayana dalam Aliran Air Sungai sebelum digunakan sebagai Bahan Pakan Unggas

Abstract: Penelitian ini bertujuan untuk mengurangi kandungan garam dan meningkatkan kandungan nutrisi rumput laut Turbinaria murayana yang direndam dalam aliran air sungai sebelum digunakan sebagai bahan pakan ternak unggas. Materi yang digunakan yaitu rumput laut jenis Turbinaria murayana yang diambil dari Pantai Sungai Nipah Kabupaten Pesisir Selatan secara acak pada 5 lokasi yang berbeda, kemudian dikomposit sebagai sampel penelitian. Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan 5 perlakuan, masing-mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
5
0
7
Order By: Relevance
“…decurrens seaweed from Sungai Nipah Coast, Pesisir Selatan Regency, West Sumatra was taken from 5 different locations, then combined to be used as research samples. These samples were taken and brought to a location or place for immersion in running water at Irrigation canal, Gunung Nago with a depth of 1.65 m and a water discharge of 0.0610 m3/s (Reski et al, 2020). The seaweed obtained, before being immersed in running water, was washed and cleaned first of the remnants of sea sand, small corals attached to the seaweed, then soaked in running water according to the immersion treatment, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…decurrens seaweed from Sungai Nipah Coast, Pesisir Selatan Regency, West Sumatra was taken from 5 different locations, then combined to be used as research samples. These samples were taken and brought to a location or place for immersion in running water at Irrigation canal, Gunung Nago with a depth of 1.65 m and a water discharge of 0.0610 m3/s (Reski et al, 2020). The seaweed obtained, before being immersed in running water, was washed and cleaned first of the remnants of sea sand, small corals attached to the seaweed, then soaked in running water according to the immersion treatment, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…According to Dewi et al, (2018) the long treatment of immersion Sargassum binderi type of seaweed in running water can reduce the dry matter content compared to without immersing. Furthermore, Reski et al, (2020) also reported that the immersion of Turbinaria murayana, brown seaweed, in running water with different immersion duration for use as broiler feed material caused a decrease in the dry matter content. Immersion of Turbinaria murayana seaweed in running water with different durations of immersion is best for the immersion for 3 hours (Reski et al, 2020).…”
Section: Dry Matter Contentmentioning
confidence: 98%
See 3 more Smart Citations